Wide band photoconductive detector based on carbon nanotubes decorated with silver nanoparticles - Y.Yousif, Taqwa; Hasan, Shahd Imad; N.Naji, Asama; Abed, Estabraq A. (Iraqi Journal of Physics, 2025)
This article outlines the methodical process of manufacturing MWCNTs/SWCNTs-Ag and analyzing wideband photodetectors using a combination of electro-explosion techniques, direct mixing, and drop casting techniques. The microstructural, optical, electrical, and photo-responsive analyses of the fabricated layers were thoroughly investigated. The topographical study specifically showed that the diameter ranges from 58 to 82 nm for Ag-NPs. However, the optical spectra of the prominent layers revealed a broad absorption phenomenon along the 200–800 nm scanning wavelength. Simultaneously, the devices fabricated from SWCNTs/MWCNTs-Ag showed significant figures of merit as a function of wavelength and illumination power (365, 460, and 808 nm) in response to the applied bias voltage from 0 to 10 V. In detail, the values attained were 0.575 and 0.06 (A/W) under the 808 nm illumination wavelength for MWCNTs-Ag and SWCNTs-Ag, respectively. The figures of merit characteristics of the fabricated devices were found to be in positive linear correlation as a function of the applied wavelength.